Judicial Challenges in Resolving Electronic Licensing Disputes before Indonesian Administrative Courts - Nova Musta'idah; Ningsih , Rahmah; Syahputra, Aan (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
This study examines the judicial challenges in resolving electronic licensing disputes arising from Decision No. 30/G/2023/PTUN.BL and Appellate Decision No. 6/B/2024/PT.TUN.PLG, where two business licenses were issued for the same object through the OSS RBA system by the DPMPTSP of Pesawaran Regency. Using a normative juridical method supplemented with empirical data from judicial interviews, the study reveals contrasting judicial approaches. The first-instance court emphasized social harmony and familial relationships, adopting a utilitarian perspective and suggesting non-adversarial settlement rather than determining the legal validity of the licenses. In contrast, the appellate court adhered to a positivist approach, focusing on procedural rigor and identifying the dual licensing as the result of an administrative validation error, as the second permit was issued without revoking the first. The study highlights that the digitalization of licensing does not automatically ensure legal certainty; rather, it introduces new challenges in judicial reasoning, evidentiary evaluation, and institutional accountability. The findings underscore the necessity of strengthening technical regulations, enhancing the administrative competence of licensing authorities, and improving administrative remedies to ensure effective judicial review within Indonesia’s digital governance framework.